Optimalisasi Dan Tantangan Strategi Pajak Dalam Lingkungan Bisnis Modern - Sihombing, Belandina Anita Sere; Fuadah, Luk Luk (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Tax planning is the central component of corporate finance strategy geared towards minimizing tax liabilities through legal means. With the current situations in business caused by globalization and digitalization, tax planning has not only been a tool of effectiveness but also has faced regulatory and ethical tests. This study aims to examine various tax schemes employed by companies and how they impact company performance and tax compliance. Adhering to a Systematic Literature Review (SLR) approach, this research analyzes 31 highest-ranked. Journal articles from reputable scholarly databases in order to identify trends, challenges, and efficiency of tax strategies. The findings indicate that efficient tax strategies can assist the financial performance of a firm, but may also evolve into aggressive tax avoidance habits in case of adequate control. This research also suggests that transparency, corporate governance, and regulatory frameworks are among the factors that contribute significantly to the impact on tax strategy effectiveness. There are contradictory results in other research when considering the relationships between business strategy, leverage, profitability, and tax avoidance. Strict regulation in certain countries has been found to promote tax compliance, but in the digital economy, the rise in tax rates does not always equal high corporate tax ratios. The conclusion of the study emphasizes the necessity of reconciling regulatory compliance and tax optimization in designing an equitable and sustainable tax system. The study is beneficial to both academics and practitioners in understanding the dynamics of tax planning strategies and how they influence the modern business landscape.